Focal MRI and Learning Disability with Reduced Automaticity - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators from the Boston Children's Hospital, Harvard Medical School, MA, performed a retrospective analysis of 1,587 children referred for a learning disability, and 127 had a focal deficit demonstrated on either a neurologic or neuropsychological evaluation.